2011
DOI: 10.1016/j.freeradbiomed.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 mediates TGF-β-induced smooth muscle α-actin via p38MAPK and serum response factor

Abstract: In contrast to other cell types, vascular smooth muscle cells modify their phenotype in response to external signals. NADPH oxidase 4 (Nox4) is critical for maintenance of smooth muscle gene expression; however, the underlying mechanisms are incompletely characterized. Using smooth muscle α-actin (SMA) as a prototypical smooth muscle gene and transforming growth factor-β (TGF-β) as a differentiating agent, we examined Nox4-dependent signaling. TGF-β increases Nox4 expression and activity in human aortic smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 77 publications
4
69
0
Order By: Relevance
“…44,46,49 These studies suggest that under conditions of TGFβ1 stimulation, p38MAPK signaling is important for VSMC differentiation ( Figure 7). The current study predicted that knockdown of p38MAPK would replicate results obtained with SB203580.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…44,46,49 These studies suggest that under conditions of TGFβ1 stimulation, p38MAPK signaling is important for VSMC differentiation ( Figure 7). The current study predicted that knockdown of p38MAPK would replicate results obtained with SB203580.…”
Section: Discussionmentioning
confidence: 93%
“…[39][40][41][42][43][44][45][46][47][48][49][50] p38 mitogen-activated protein kinase (p38MAPK) is among the signaling pathways shown to be pivotal for TGFβ1-induced VSMC differentiation. 44,46,49,51 p38MAPK comprises 4 different isoforms encoded in 4 distinct gene loci. Among these isoforms, p38MAPKα (MAPK14) and p38MAPKβ (MAPK11) have received most attention in terms of expression and activity, based on their high sensitivity to the selective inhibitors, SB203580 and SB202190.…”
Section: Long Et Al P38mapk Regulation Of Vsmc Differentiation 379mentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of p38 MAPK is required for the expression of genes encoding SMC contractile markers and for inhibiting VSMC cell cycle progression. [9][10][11] Recent studies have reported that p38 MAPK is involved in SRF and myocardin expression. During cardiovascular development and VSMC phenotypic modulation, p38 MAPK plays a key role in inducing myocardin expression by activating myocyte enhancer factor 2, an upstream transcription factor of myocardin.…”
Section: Discussionmentioning
confidence: 99%
“…8 Because the activation of the p38 MAPK pathway is involved in phenotypic switching and cell cycle arrest of VSMCs, we investigated whether p38 MAPK is required for FGF12-induced phenotypic changes in VSMCs. [9][10][11] Western blotting showed that phosphorylation of p38 MAPK was profoundly enhanced in adenovirus FGF12-transfected HASMCs compared with control cells (Figure 7A). Inhibition of the p38 MAPK pathway blocked FGF12-induced upregulation of myocardin and SRF …”
Section: Fgf12 Induces the Quiescent And Contractile Phenotypes Of Hamentioning
confidence: 99%